Tn-seq screens in Candida glabrata treated with echinocandins and ibrexafungerp reveal pathways of antifungal resistance and cross-resistance - Timothy J. Nickels; Kyle W. Cunningham (mSphere, 2025)
ABSTRACT Candida glabrata (also known as Nakaseomyces glabratus) is the second most common cause of candidiasis, next to Candida albicans, and is rising in prevalence due to intrinsic and acquired mechanisms of antifungal resistance. This study utilizes transposon mutagenesis and deep sequencing (Tn-seq) to explore mechanisms of resistance to four different echinocandins (micafungin, anidulafungin, rezafungin, and caspofungin) and a non-echinocandin inhibitor (ibrexafungerp) of beta-1,3-glucan synthase (GS) in the BG2 strain background. Contrary to the other antifungals, caspofungin susceptibility exhibited high dependence on sphingolipid genes and low dependence on mitochondrial genes. Numerous deficiencies in mitochondrial genes increased fitness in micafungin, anidulafungin, rezafungin, and ibrexafungerp largely through effects on Pdr1, a stress-activated transcription factor known to promote fluconazole resistance. Several targets of Pdr1 (RTA1, LAF1, LAC1, IPT1, and RSB1) altered resistance to one or more of the GS inhibitors when overexpressed individually. Though Gal11 and other subunits of the mediator complex were necessary for the Pdr1 effects, an inhibitor of Gal11 (iKIX1) did not synergize with micafungin due to off-target antagonistic effects. Substantial variation was observed in the genetic resistance spectra for the different GS inhibitors within the BG2 strain background and comparison to the CBS138 strain background. The intra-strain variation was linked to gene deficiencies thought to alter phospholipid and ergosterol composition or asymmetry in cellular membranes. The findings generally support and extend earlier hypotheses that a lipid code governs GS inhibition and antifungal susceptibility in C. glabrata.IMPORTANCEEchinocandins and ibrexafungerp are important antifungals that target the same fungal enzyme. When the fungus acquires resistance to one of these antifungals, it may or may not exhibit cross-resistance to the others. This study investigates how every gene in the pathogenic yeast Candida glabrata contributes to resistance and cross-resistance to all five antifungals of this type. It offers new insights into how each antifungal interacts with the target enzyme and identifies the antifungals where cross-resistance is common or rare, providing guidance on the sequences and combinations that may be most effective in clinical settings.